Sarcoidosis-Associated Pulmonary Hypertension - Yoshitaka Morimatsu; Nobuhiro Tahara; Masaki Okamoto; Munehisa Bekki; Atsuko Tahara; Yoshiko Eto; Tadahiro Kugai; Yuki Koga; Shoko Maeda-Ogata; Akihiro Honda; Sachiyo Igata; Yoshiaki Zaizen; et al. (Medicina, 2025)
Sarcoidosis is a granulomatous disorder of unknown etiology characterized by multisystem non-caseating granulomas. Pulmonary hypertension (PH) is a well-known complication of sarcoidosis and is associated with increased morbidity and mortality. The actual epidemiology of sarcoidosis-associated PH (SAPH) remains unknown, and its pathogenesis has not been fully elucidated. SAPH is classified under the miscellaneous category (group 5 of the PH classification). The clinical presentation of SAPH is variable and not always proportional to the severity of sarcoidosis. Appropriate management for SAPH by an experienced physician is important; however, no treatment algorithm for SAPH has been established. Lung transplantation should be considered in refractory cases. Pulmonary arterial hypertension-specific vasodilators targeting the endothelin pathway, nitric oxide pathway, and prostacyclin pathway have improved the clinical functions and hemodynamics in some patients with SAPH.